1998
DOI: 10.1136/jnnp.65.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in temporal N-acetylaspartate and creatine (or choline) ratio in temporal lobe epilepsy: does this 1H-magnetic resonance spectroscopy finding mean poor seizure control?

Abstract: Conclusions-There were reduced temporal NAA/Cr and NAA/Cho ratios, suggesting neuronal loss or damage, associated with past or present poor seizure control in the patients with temporal lobe epilepsy, but it does not exclude the possibility of a future complete seizure control (seizure free patients with temporal lobe epilepsy at the time of 1 H-MRS). This study warrants further 1 H-MRS investigation with a larger series of patients with temporal lobe epilepsy. (J Neurol Neurosurg Psychiatry 1998;65:518-522)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
0
17
1
1
Order By: Relevance
“…Alternatively, several groups have reported decreased NAA levels estimated by proton magnetic resonance spectroscopy in epileptic patients correlating with increased seizure frequency (Vainio et al, 1994;Vermathen et al, 1997;Mendes-Ribeiro et al, 1998), which appears inconsistent with our results. However, this apparent discrepancy might be explained by the different location of NAA between human epileptic patients and NAA-injected rats.…”
Section: Discussioncontrasting
confidence: 57%
“…Alternatively, several groups have reported decreased NAA levels estimated by proton magnetic resonance spectroscopy in epileptic patients correlating with increased seizure frequency (Vainio et al, 1994;Vermathen et al, 1997;Mendes-Ribeiro et al, 1998), which appears inconsistent with our results. However, this apparent discrepancy might be explained by the different location of NAA between human epileptic patients and NAA-injected rats.…”
Section: Discussioncontrasting
confidence: 57%
“…This does not imply that patients with abnormal NAA/Cr ratios could not achieve seizure control. Mendes-Ribeiro et al (53) reported single voxel temporal lobe 'H-MRS findings in 10 seizure-free TLE patients treated with AEDs. Eight patients had normal NAA/Cr values; however, two patients had significant NAA/Cr reduction despite a long period of seizure freedom (3 years) using AEDs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MR spectroscopy has been used in the evaluation of mesial temporal sclerosis (22). The use of single-voxel proton spectroscopy adds about 10 or 15 minutes to the total examination time and shows decreased N-acetylaspartateto-creatine ratios in the hippocampus on the affected side.…”
Section: Complex Partial Seizuresmentioning
confidence: 99%